The cytoarchitecture of the human anterior cingulate cortex and its involvement in mood disorder - Gittins, R; Gittins, R A (2003)
﻿ The biological mechanisms proposed to underlie primary mood disorder do not usually include a neuropathological component. Over recent years, a significant imaging literature attests to structural abnormalities in various brain regions in mood disorder, and has encouraged neuropathological investigations. Although the neuropathological understanding of mood disorder is still rudimentary, structural correlates have begun to emerge. The studies described in this thesis investigate the neuropathology of the anterior cingulate cortex in mood disorder. The anterior cingulate cortex is extremely diverse and complex, particularly in respect to its cytoarchitecture and functional organisation. These details are important when considering the precise localisation and clinical correlates of the neuropathological changes of this region in disease. Accordingly, I performed a detailed analysis of the cytoarchitecture of the human anterior cingulate cortex, as a prelude to investigations of this region in mood disorder. I measured several morphometric parameters within different anatomical levels and both hemispheres of the anterior cingulate cortex. Overall I found a clear distinction in the cellular composition of the supragenual and subgenual regions of the anterior cingulate cortex. The subgenual region demonstrated a lower glial density and smaller neurons in comparison to the supragenual region. A modest difference in neuronal density was also observed, with a higher density in the deep layers of the subgenual cortex compared to the deep layers of the supragenual cortex. Total cortical depth was also thinner in the subgenual region. This work may have important implications for the interpretation of imaging and pathological data in mood disorder. To assess the cytoarchitecture of this brain region in mood disorder, I examined several morphometric indices in addition to various parameters of gene expression in post mortem brains. I found a range of cytoarchitectural abnormalities in the supragenual anterior cingulate cortex in mood disorder. The most prominent change included a reduction in glial density, which was evident in all layers of the cortex. Glial fibrillary acidic protein was also reduced, providing some evidence for astrocyte involvement. Various neuronal changes were also observed in the mood disorder group. These included layer-specific reductions in pyramidal neuron density and a modest change in the density of cairetinin-immunoreactive neurons. I did not find any evidence supporting synaptic pathology in the anterior cingulate cortex in mood disorder. These findings extend previous evidence of cytoarchitectural alterations in the anterior cingulate cortex in mood disorder and in particular emphasise the prominent involvement of glial cells in the neuropathology of this disease. The origins of the glial (and neuronal) deficits in mood disorder remain to be established, but they are likely to have pathophysiological consequences.